Additive Manufacturing of Poly(propylene) by Means of Melt Extrusion - Hertle, Sebastian; Drexler, Maximilian; Drummer, Dietmar (Macromolecular Materials and Engineering, 2016)
Keywords: additive manufacturing; fusion bonding; melt extrusion; poly(propylene) (PP); thermoplastics

Analysis of time dependent thermal properties for high rates in selective laser sintering - Wudy, Katrin; Drexler, Maximilian; Lanzl, Lydia; Drummer, Dietmar (Proceedings of 6th International Conference on Additive Technologies, 2016)

A novel process for production of spherical PBT powders and their processing behavior during laser beam melting - Schmidt, Jochen; Sachs, Marius; Zhao, Meng; Fanselow, Stephanie; Wudy, Katrin; Drexler, Maximilian; Drummer, Dietmar; Wirth, Karl-Ernst; Peukert, Wolfgang (31st International Conference of the POLYMER PROCESSING SOCIETY, 2016)
Additive manufacturing processes like laser beam melting of polymers are established for production of prototypes and individualized parts. The transfer to other areas of application and to serial production is currently hindered by the limited availability of polymer powders with good processability. Within this contribution a novel process route for the production of spherical polymer micron-sized particles of good flowability has been established and applied to produce polybutylene terephthalate (PBT) powders. Moreover, the applicability of the PBT powders in selective laser beam melting and the dependencies of process parameters on device properties will be outlined. First, polymer micro particles are produced by a novel wet grinding method. To improve the flowability the produced particles the particle shape is optimized by rounding in a heated downer reactor. A further improvement of flowability of the cohesive spherical PBT particles is realized by dry coating. An improvement of flowability by a factor of about 5 is achieved by subsequent rounding of the comminution product and dry-coating as proven by tensile strength measurements of the powders. The produced PBT powders were characterized with respect to their processability. Therefore thermal, rheological, optical and bulk properties were analyzed. Based on these investigations a range of processing parameters was derived. Parameter studies on thin layers, produced in a selective laser melting system, were conducted. Hence appropriate parameters for processing the PBT powders by laser beam melting, like building chamber temperature, scan speed and laser power have been identified.
Keywords: downer reactor; dry coating; polybutylene terephthalate (PBT); selective laser beam melting of polymers; wet grinding

Characterization of polymer materials and powders for selective laser melting - Wudy, Katrin; Drummer, Dietmar; Drexler, Maximilian (Proceedings of the Polymer Processing Society 29th Annual Meeting, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KT.charac

Degradation behaviour of PA 12 powders in laser sintering - Drummer, Dietmar; Kühnlein, Florian; Drexler, Maximilian (Proceedings of the 4th International Conference on Additive Technologies (ICAT 2012), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.degrad

Density of Laser Molten Polymer Parts as Function of Powder Coating Process during Additive Manufacturing - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (New Paradigm of Particle Science and Technology Proceedings of The 7th World Congress on Particle Technology, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-KT.densit

Density of Laser Molten Polymer Parts as Function of Powder Coating Process during Additive Manufacturing - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (Procedia Engineering, 2015)

Derivation of Heating Rate Dependent Exposure Strategies for the Selective Laser Melting of Thermoplastic Polymers - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (Proceedings of the Polymer Processing Society 30th Annual Meeting, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.deriva

Derivation of heating rate dependent exposure strategies for the selective laser melting of thermoplastic polymers - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (AIP Conference Proceedings, 2015)

Effects of the powder bulk density on the porosity of laser molten thermoplastic parts - Drexler, Maximilian; Drummer, Dietmar; Wudy, Katrin (Proceedings of the Polymer Processing Society 29th Annual Meeting, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KT.effect

Effects on the density distribution of SLS-parts - Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (Physics Procedia 39, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.effect

Einfluss der Scangeschwindigkeit auf die Bauteileigenschaften pulver- und strahlbasierter Verfahren - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (RTejournal - Forum für Rapid Technologie, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KT.einflu

Einfluss des Pulverauftragsprozesses auf den selektiven Strahlschmelzprozess thermoplastischer Kunststoffe - Drexler, Maximilian; Drummer, Dietmar; Wudy, Katrin (Tagungsband / Digital Proceedings RapidTech 2015, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KT.einflu

Fundamental investigation of laser beam melting of polymers for additive manufacture - Laumer, Tobias; Wudy, Katrin; Drexler, Maximilian; Amend, Philipp; Drummer, Dietmar; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2014)
By selective laser sintering (SLS), polymer powders are molten layer by layer to build conventional prototypes or parts in small series with geometrical freedom that cannot be achieved by other manufacturing technologies. The SLS process is mainly defined by the beam-matter interaction between powder material, laser radiation and different material characteristics by itself. However the determination of these different material characteristics is problematic because powder material imposes certain requirements that cannot sufficiently be provided by conventional measurement methods. Hence new fundamental investigation methods to determine the optical and thermal material characteristics like the thermal diffusivity, thermal conductivity, or the influence of different heating rates on the melting behavior are presented in this paper. The different analysis methods altogether improve the process of understanding to allow recommendations for the future process controlling. (C) 2014 Laser Institute of America.
Keywords: additive manufacturing; laser beam melting of polymers; multi-material parts

Fundamental investigation of laser beam melting of polymers for additive manufacture (vol 26, 042003, 2014) - Laumer, Tobias; Wudy, Katrin; Drexler, Maximilian; Amend, Philipp; Drummer, Dietmar; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2015)

Fundamental investigation of part properties at accelerated beam speeds in the selective laser sintering process - Lexow, Matthias; Drexler, Maximilian; Drummer, Dietmar (Rapid Prototyping Journal, 2017)
Purpose - Despite the recent progress in basic process understanding considering the selective laser sintering (SLS) of thermoplastics, several aspects of the mechanisms of the beam and powder interaction are not fully understood yet. Recent studies covered the correlation of mechanical properties and part density with the heating rate. The surface roughness of the test specimens was also considered but showed no distinct relation to the part mechanics. The purpose of this paper is to provide a new fundamental model for describing the decreasing mechanical properties with increasing beam speed.Design/methodology/approach - While the dependence of mechanical properties with total energy input during exposure is well published, the correlation of the exposure speed with the degree of particle melt (DPM) is the subject of the present study. The DPM is accessible through differential scanning calorimetry measurements. Supporting the previously introduced method of the core-peak height, the interpretation via the core-peak area is proposed as a means to ascertain the melting behaviour for different processing conditions. Further support of the observations is given by x-ray computed tomography and microscopy which allows for a correlation with the respective porosity and inner structure of the parts.Findings - The authors show a novel way of describing the decreasing mechanical properties with increasing speed of energy input by showing the dependence of the DPM on the heating rate during exposure.Practical implications - The results offer an addition to the understanding considering the reliability and reproducibility of the SLS process.Originality/value - The paper extends the existing models of the time-dependent material behaviour, which allows for the derivation of new efficient and stable process strategies.
Keywords: Selective laser sintering; Mechanical properties; Porosity; Degree of particle melt; Heating rate; Part density

Grundlegende Betrachtungen zur Modellierung transienter thermischer Vorgänge beim selektiven Lasersintern von Thermoplasten - Rietzel, Dominik; Drexler, Maximilian; Drummer, Dietmar (RTejournal - Forum für Rapid Technologie, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KT.grundl

Impact of Heating Rate During Exposure of Laser Molten Parts on the Processing Window of PA12 Powder - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (Physics Procedia, 2014)
The additive component manufacturing by selective beam melting of thermoplastic polymer powders can be divided essentially into the following sub-processes: Powder coating, exposure and material consolidation. The mechanical and geometrical properties of a part produced by the selective melting of polymer powders depend to a large extent on these sub-processes. To increase process repeatability basic knowledge about the mutual interactions within the sub-process is of major interest. In the following article the exposure process is focused. Therefore the time dependent energy input into the powder bed is analyzed in its impact on the usable processing window of PA12 powder. Thereby parameters like surface temperature, density and strength of molten layers as well as complex body specimens are quantified for varying exposure heating rates. Therefore methods of statistical design of experiments are used. Due to these investigations the derivation of new, the time dependent material behavior of polymers fitting processing strategies is possibl
UnivIS-Import:2015-07-08:Pub.2014.tech.FT.FT-KT.impact
Keywords: Heating rate; Part density; Selective laser melting

Influence of degradation behavior of polyamid 12 powders in laser sintering process on produced parts - Wudy, Katrin; Drummer, Dietmar; Drexler, Maximilian (Proceedings of the Polymer Processing Society 29th Annual Meeting, 2014)
To correlate these results of the model experiment with real manufacturing process laser sintering experiments are done. PA12 powder is used for several building processes with refreshing. Produced specimens and resulting partcake powder are analyzed and correlated to the results of model experiment. Correlating effects, regarding process relevant material properties as well as aging influenced mechanical properties of specimens can be detected.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KT.influe_0
Keywords: degradation; polyamide 12; selective laser melting of polymers

Influence of Energy Input on Degradation Behavior of Plastic Components Manufactured by Selective Laser Melting - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (Proceedings 5th International Conference on Additive Technologies - iCAT2014, 2014)
Additive manufacturing techniques, such as selective laser melting of plastics, generate components directly from a CAD data set without using a specific mold. High building chamber temperatures in combination with long building times lead to physical and chemical degradation of the surrounding powder and the manufactured component in the case of selective laser melting of polyamide 12 (PA12). Thus the following investigations show the influence of energy densities on mechanical properties as well as on the aging behavior of the manufactured components. Therefore several building processes with varying energy densities will be conducted. Aged polymer components were analyzed with physical, thermo analytical and mechanical methods with regards to their process relevant material properties. Considered material properties for example are phase transition temperatures, melting viscosity or molecular weight. The basic understanding of the influence of energy input on material properties will lead to new process strategies with minimized polymer degradation.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.influe_2
Keywords: Aging; Energy density; Polyamide 12; Selective laser melting

Influence of Energy Input on Degradation Behavior of Polyamide 12 during selective Laser Melting Process - Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (DDMC 2014, Proceedings of the Fraunhofer Direct Digital Manufacturing Conference, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.influe

Influence of powder coating on part density as a function of coating parameters - Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (4th International Conference on Additive Technologies, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.influe

Influence of temperature fields on the processing of polymer powders by means of laser and mask sintering technology - Rietzel, Dominik; Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (Twenty Second Annual International Solid Freeform Fabrication Symposium An Additive Manufacturing Conference, 2011)
Besides their high potential for individual series-production, powder and beam based additive manufacturing technologies, like laser and mask sintering, are in general still restricted to prototyping applications. This is a result of multiple limitations concerning part properties (e.g. mechanical and geometrical), their insufficient reproducibility due to transient thermal conditions and the limited range of available materials. The main focal point of this paper is to show the influencing parameters (e.g. temperature fields in the building chamber) of powder-based thermoplastic processing technologies on part properties, like porosity and surface quality, and on the processability of further new polymers (e.g. polypropylene and polyoxymethylene
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.influe_6

Interaction between Time Dependent Exposure Strategies and Part Positioning within Selective Laser Melting Process of Plastics - Drexler, Maximilian; Drummer, Dietmar; Wudy, Katrin (International Journal of Recent Contributions from Engineering, Science & IT, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-KT.intera

Investigations on the degradation behaviour of PA 12 plastic powders - Influence of high temperatures on the moleculare weight - Drummer, Dietmar; Kühnlein, Florian; Meister, Steve; Drexler, Maximilian (Proceedings of the 13th RAPDASA annual international Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.invest

Langzeitverhalten von Polyamid 12 Pulver zur Verarbeitung mittels selektivem Laserstrahlschmelzen - Wudy, Katrin; Drummer, Dietmar; Drexler, Maximilian (Technomer 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KT.langze

Laser-high-speed-DSC: Process-oriented thermal analysis of PA 12 in selective laser sintering - Lanzl, Lydia; Wudy, Katrin; Drexler, Maximilian; Drummer, Dietmar (Physics Procedia, 2016)

Long-term properties of laser sintered parts of polyamide 12 - Influence of storage time and temperature on the ageing behaviour - Drummer, Dietmar; Harder, Ron; Witt, Gerd; Wegner, Andreas; Wudy, Katrin; Drexler, Maximilian (Proceedings 5th International Conference on Additive Technologies - iCAT2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.longte

Long-term Properties of Laser Sintered Parts of Polyamide 12 - Influence of Storage Time and Temperature on the Aging Behavior - Drummer, Dietmar; Harder, Ron; Witt, Gerd; Wegner, Andreas; Wudy, Katrin; Drexler, Maximilian (International Journal of Recent Contributions from Engineering, Science & IT, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-KT.longte

Materialalterung beim Rapid Manufacturing - Alterungsverhalten von Kunststoffpulvern beim selektiven Strahlschmelzen - Wudy, Katrin; Kühnlein, Florian; Drummer, Dietmar; Drexler, Maximilian (GIT Labor-Fachzeitschrift, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KT.materi

Modeling of Transient Thermal Conditions During Selective Laser Melting - Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (1st International Conference on Thermo-Mechanically Graded Materials, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.modeli

Modelling of the Aging Behavior of Polyamide 12 Powder during Laser Melting Process - Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (Proceedings of the Polymer Processing Society 30th Annual Meeting, 2015)
Concerning individualization, the requirements to products have increased. Additive manufacturing technologies, such as selective laser melting allow manufacturing of complex parts without tools and forms. Due to this additive manufacturing processes comply, in opposite to conventional techniques, with these increased demands on processing technology. Due to the high temperature during processing, a degradation of the used plastic powder occurs. The non-molten material in the building chamber, the so-called partcake, can be removed after building from the finished component and reused for another process. To realize reproducible part properties refreshing of pancake powder with 30 up to 50 % virgin powder is necessary. However, these refreshing strategies lead to varying component properties due to an undefined aging state. Previous investigations on oven aged powder for selective laser melting showed for short periods of storage near the melting point thermally induced post condensation is the predominate aging effect. Due to post condensation the molecular weight and thus the viscosity increases. This paper focuses on the modeling of the post condensation process to define the aging state of polyamide 12 powder in laser melting process. Therefore the rheological behavior of PA 12 powder in dependency of time and temperature is investigated. Isothermal viscosity measurements are conducted in order to describe the post condensation reaction with a model. With knowledge of the kinetics of the post condensation reaction the state of aging can be predicted in a second step. Thus expected useful life of the powder can be calculated in dependency of the building chamber temperature. These results are then compared with viscosity values of defined aged PA 12 powder to validate the determined model.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.modell
Keywords: Selective Laser Melting; Aging; Modelling; Polyamide 12

Modelling, simulation and experimental validation of heat transfer in selective laser melting of the polymeric material PA12 - Riedlbauer, Daniel-Rouven; Drexler, Maximilian; Drummer, Dietmar; Steinmann, Paul; Mergheim, Julia (Computational Materials Science, 2014)
One of the most promising additive manufacturing techniques is selective laser melting of semi-crystalline thermoplastic powders. In this process the powder is fused in defined, locally-restricted points in the current powder layer by the energy input of a laser beam and, thereby, bonded to the already fused material of previous layers. In this way geometrically complex parts are constructed layer-by-layer. The accuracy of the process and the properties of the resulting parts depend on numerous process parameters and their interactions. To improve the process strategy and to reduce, e.g. eigenstresses and warpage a thorough understanding of the influence of various process parameters is required. In the present contribution one step in this direction is done by analysing the laser energy input into a powder bulk for different process parameters by comparing temperature distributions and the size of melting pools. Experiments with single-line specimens are conducted, analysed and compared to numerical results from finite element simulations of the highly nonlinear thermal problem. © 2014 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-TM.modell_2
Keywords: Additive manufacturing; Heat transfer simulation; Selective laser melting

Polymer powder production for laser melting through immiscible blends - Drummer, Dietmar; Medina Hernandez, Martha; Drexler, Maximilian; Wudy, Katrin (Procedia Engineering, 2015)
hurdle in procuring suitable materials for laser melting. Obtaining the correct particle size and morphology is vital as the powder properties influence both processing ability and the final characteristics of the part. The exploitation of the immiscibility of special polymer blends during extrusion or kneading process represent a path to generate powder with desired morphology and particle size. Key issues to consider are: the feasibility to separate the mixture, properties and processing limitations of the constituents. In this paper it is studied the resulting morphological structure of PA12-PEG and PA12-Polyvinil Alcohol (PVA) blends. PA12 is by far the most widely used polymer in laser melting and, PEG and PVA are water soluble, these factors make the investigation of their blends and possibilities to control their morphology a pretty interesting path to produce quality powder for laser melting. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Powder production; particles morphology; immiscible blends

Rapid-Manufacturing-Process for Elastomeric Components - Launhardt, Martin; Drexler, Maximilian; Drummer, Dietmar (International Journal of Recent Contributions from Engineering, Science & IT, 2015)

Resulting melt-pool-shape during selective beam melting of thermoplastics as function of energy input parameters - Drummer, Dietmar; Drexler, Maximilian; Wudy, Katrin (DDMC 2014, Proceedings of the Fraunhofer Direct Digital Manufacturing Conference, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.result

Selective laser melting of polyamide 12: A holistic approach for the modeling of the aging behavior - Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (Proceedings 5th International Conference on Additive Technologies - iCAT2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.select

Selective Laser Melting of Polymer Powder - Part Mechanics as Function of Exposure Speed - Drexler, Maximilian; Lexow, Matthias; Drummer, Dietmar (Physics Procedia, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.FT.FT-KT.select
Keywords: heating rate; part density; Selective laser melting; tensile properties

Selective laser melting of polymers: Influence of powder coating on mechanical part properties - Drexler, Maximilian; Greiner, Sandra; Lexow, Matthias; Lanzl, Lydia; Wudy, Katrin; Drummer, Dietmar (Journal of Polymer Engineering, 2018)
Keywords: selective laser sintering of polymers; mechanical properties; powder coating; coating speed

Selektives Laserstrahlschmelzen von Kunststoffen - Modellierung des Temperaturhaushaltes und Einfluss auf resultierende Bauteileigenschaften - Drexler, Maximilian; Drummer, Dietmar; Wudy, Katrin; Riedlbauer, Daniel-Rouven; Steinmann, Paul; Mergheim, Julia (2. Industriekolloquium des SFB 814, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KT.selekt

Selektives Strahlschmelzen von Kunststoffen - Ganzheitliche Prozessbetrachtung zur gezielten Optimierung von Bauteileigenschaften - Drexler, Maximilian; Wudy, Katrin; Drummer, Dietmar (3. Industriekolloquium des SFB 814, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.FT.FT-KT.selekt

Selektives Strahlschmelzen von Polymer-Blends: Prozess- und Werkstoffanforderungen - Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (Tagungsband / Digital Proceedings RapidTech 2015, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KT.selekt

Sintering Study of Polyamide 12 Particles for Selective Laser Melting - Zhao, Meng; Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (Proceedings 5th International Conference on Additive Technologies - iCAT2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KT.sinter_5

Sintering Study of Polyamide 12 Particles for Selective Laser Melting - Zhao, Meng; Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (International Journal of Recent Contributions from Engineering, Science & IT, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-KT.sinter

Strategien zur Realisierung konstanter Pulver- und Bauteileigenschaften beim selektiven Laserstrahlschmelzen von Kunststoffen - Wudy, Katrin; Drexler, Maximilian; Drummer, Dietmar (2. Industriekolloquium des SFB 814, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KT.strate

Untersuchung des Schmelz- und Sinterprozesses von Polyamid 12 beim selektiven Strahlschmelzen - Zhao, Meng; Drummer, Dietmar; Wudy, Katrin; Drexler, Maximilian (Tagungsband / Digital Proceedings RapidTech 2015, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KT.unters

Untersuchungen zum Potential der Pulververdichtung durch den Pulverauftrag beim selektiven Laserstrahlschmelzen von Kunststoffen - Greiner, Sandra; Lanzl, Lydia; Wudy, Katrin; Drexler, Maximilian; Drummer, Dietmar (Proceedings of Rapid Tech 2017, 2017)